2007
DOI: 10.1007/s00127-007-0299-4
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety disorder above and below the diagnostic threshold: prevalence, comorbidity and impairment in the general population

Abstract: Our results suggest that social anxiety below the diagnostic threshold is clearly associated with adverse outcomes. Prospective designs should examine the exact temporal and possible causal pathways of this burden in order to inform prevention and early intervention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
186
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(206 citation statements)
references
References 41 publications
9
186
1
10
Order By: Relevance
“…Studies based on the DSM-III-R classification found 1-month prevalence between 2% and 7%, 12-month prevalence between 4.8% and 11.1%, and lifetime prevalence between 4.0% and 16% [9][10][11][12][13][14]. Prevalences based on DSM-IV classification show a one-month prevalence between 1.6% and 15.6%, 12-month prevalence between 1.2% and 7.2% and lifetime prevalence between 2.3% and 7.3% [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 95%
“…Studies based on the DSM-III-R classification found 1-month prevalence between 2% and 7%, 12-month prevalence between 4.8% and 11.1%, and lifetime prevalence between 4.0% and 16% [9][10][11][12][13][14]. Prevalences based on DSM-IV classification show a one-month prevalence between 1.6% and 15.6%, 12-month prevalence between 1.2% and 7.2% and lifetime prevalence between 2.3% and 7.3% [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 95%
“…They are also more likely to stay in jobs below their level of education [Lampe et al, 2003;Ruscio et al, 2008]. Individuals with SAD often suffer from comorbid mental disorders which further aggravate their psychological well-being and their quality of life [e.g., Fehm et al, 2008]. SAD is not only associated with high personal suffering but also with high societal costs which further emphasizes the need for effective treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Unreasonably strong fears were found in 22.3% of male and in 32.2% of female adolescents aged 14 to 24 years [115]. Similarly, at least one fifth of adults reported unreasonable strong fears [31].…”
Section: Facets Of Social Anxiety: Shyness Social Fears Social Phobmentioning
confidence: 95%
“…Mean duration for SAD symptoms ranges from 19 to 21 years in clinical studies, and from 19 to 25 years in community studies [31,113]. SAD does therefore not appear to be a transitory condition in adolescence and young adulthood.…”
Section: Natural Course: Age Of Onset Duration Remission and Pattermentioning
confidence: 97%
See 1 more Smart Citation